The Effect of Covid-19 Pandemic on Large-cap Stocks in Malaysia - Asmah Mohd Jaapar; Nurhatiah Ahmad Chukari; Siti Nurin Salwa Tarmizi (USIM Press, 2024)
Covid-19 that emerged in Wuhan, China and spread to Malaysia starting from 25th January 2020 has changed people’s lives and impacted the world’s economy, including the stock markets. The study investigates the impact of the Covid-19 pandemic on the stock returns in Malaysia by using a sample of thirty (30) constituents of FBM KLCI. The study utilises Malaysia’s daily Covid-19 new cases, death cases, cumulative cases, and cumulative death cases, as well as Singapore new cases and death cases. The impact is observed from 31st December 2019 until 9th June 2020 using the panel regression model. The results show a significant positive but small impact of Covid-19 variables on the stocks’ returns except for Singapore daily cases and death cases, which were negative. The study also identifies that the Malaysian stock market is more sensitive to Covid-19 local death cases during the pandemic.